Intelligent Integrated Digital Platform InSilicoKDD in Support of Precision Medicine for Scientific Research - lamenka Borovska, Iliyan Kordev, Boris Borowsky (International Journal of Advanced Science and Technology, 2020)
The paper presents intelligent integrated digital platform InSilicoKDD based on scientific workflows in support of precision medicine designed, implemented and deployed at the Faculty of Applied Mathematics and Informatics, Technical University of Sofia. The platform is built upon our method for adaptive in silico knowledge data discovery and intelligent decision making as well as integrated approach to combine and analyze digital data at all stages of breast cancer progress, deploying modern in silico KDD methods and technologies. The conceptual architectural design of InSilicoKDD platform is presented and the software prototype revealed. Functionality and efficiency of InSilicoKDD platform have been verified on the basis of experimentation for the breast cancer issue by configuring and executing scientific workflows encompassing machine learning models for diagnostics and prediction, data sets with results of the biopsy of the cells in the patient’s tumor as well as breast cancer risk assessment models